Relevance of the Diversity among Members of the Trypanosoma Cruzi Trans-Sialidase Family Analyzed with Camelids Single-Domain Antibodies - Ratier, Laura (Public Library of Science, 2008)
The sialic acid present in the protective surface mucin coat of Trypanosoma cruzi is added by a membrane anchored trans-sialidase (TcTS), a modified sialidase that is expressed from a large gene family. In this work, we analyzed single domain camelid antibodies produced against trans-sialidase. Llamas were immunized with a recombinant trans-sialidase and inhibitory single-domain antibody fragments were obtained by phage display selection, taking advantage of a screening strategy using an inhibition test instead of the classic binding assay. Four single domain antibodies displaying strong trans-sialidase inhibition activity against the recombinant enzyme were identified. They share the same complementarity-determining region 3 length (17 residues) and have very similar sequences. This result indicates that they likely derived from a unique clone. Probably there is only one structural solution for tight binding inhibitory antibodies against the TcTS used for immunization. To our surprise, this single domain antibody that inhibits the recombinant TcTS, failed to inhibit the enzymatic activity present in parasite extracts. Analysis of individual recombinant trans-sialidases showed that enzymes expressed from different genes were inhibited to different extents (from 8 to 98%) by the llama antibodies. Amino acid changes at key positions are likely to be responsible for the differences in inhibition found among the recombinant enzymes. These results suggest that the presence of a large and diverse trans-sialidase family might be required to prevent the inhibitory response against this essential enzyme and might thus constitute a novel strategy of T. cruzi to evade the host immune system.